Investor Sentiment for Real Assets: The Case of Dry Bulk Shipping Market - Papapostolou, Nikos C.; Nomikos, Nikos K.; Pouliasis, Panos K.; Kyriakou, Ioannis (Review of Finance, 2014)
Abstract We investigate the role of sentiment and its implications for real assets. Using shipping sentiment proxies that capture market expectations, valuation, and liquidity, we construct sentiment indices for the dry bulk shipping market. Evidence suggests that sentiment affects the monthly returns of real assets. The empirical findings also show that market sentiment serves as a contrarian indicator for future cycle phases in all sectors. Furthermore, a sentiment-based trading simulation exercise on the sale and purchase of vessels shows that investors can benefit from higher returns compared to the buy-and-hold benchmark, while partially offsetting the highly volatile nature of the shipping industry.